Student perspectives of gender-based homicides in nigerian universities - Bolanle Oriola; Melanie Moen (SAPIENTIAE)
Gender-related homicide, especially femicide, is becoming a global challenge. Past studies have concentrated efforts toward alleviating these tragedies in homes, families, and society, with little attention on educational spaces such as universities. In Nigeria, for instance, cases of femicide have continued to rise, with reports claiming that such acts are a result of money-making rituals. This current study investigated the causes and effects of gender-related homicides as well as their preventive measures as perceived by undergraduates in three Nigerian southwest universities. Underpinned by the feminist theory, the study adopted the survey research design. The study population comprised students in Nigerian southwestern universities, with a sample of 315 undergraduates purposively selected from the sampled universities. The Perceived Causes, Effects, and Preventive Measures of Gender-Related Homicide Questionnaire (PCEPMGHQ) was used for data collection (α=0.96, 0.94, 0.94) for the sub-sections of the questionnaire, which was administered via Google Forms. Data were analysed using descriptive statistics and a t-test at a 5% significance level. Results indicate mental health challenges, feelings of abandonment, financial difficulties, substance and alcohol abuse, home-related factors, history of abuse, and violent relationships as students perceived dominant causes of gender-related homicides. Trauma, grief, stigmatization, and psychological and emotional distress were the effects of gender-related homicides highlighted by the respondents who advocated several preventive measures.